Neutral heel lateral push test: The first clinical examination of spring ligament integrity. Issue 2 (June 2015) - Pasapula, Chandra; Devany, Adam; Magan, Ahmed; Memarzadeh, A.; Pasters, V.; Shariff, S.
Highlights Spring ligament is the primary supporting structure against planovalgus deformity. We examined 21 cadaveric specimens in a standardised and reproducible manner. Mean lateral translation increased most significantly when spring ligament released. Neutral heel lateral push test can determine spring ligament integrity.